Strengthening Inclusive Production Management Skills to Achieve Financial Independence for Surabaya's Smes - Mamduh, Achmad; Gunartin; Nurdiana, Iva (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This study examines how strengthening inclusive production management skills helps small and medium- sized enterprises (SMEs) in Surabaya become more financially independent. Surabaya, one of the national economic growth centres, displays a competitive urban economic dynamic that requires extraordinary adaptation to the transformation of production systems. SMEs face numerous challenges, such as a lack of capital and technology, as well as insufficient management capabilities to run production processes fairly and effectively. Using phenomenological methodology as part of a qualitative approach, this study investigates the subjective experiences of SME actors when internalising the principles of efficiency and inclusion in production management. Participatory observation, in-depth interviews, and field documentation analysis were the methods used to collect data. The study found that inclusive production management practices, which include the implementation of production digitization, cross-stakeholder collaboration, and business community participation, are essential for improving the financial independence and competitiveness of SMEs. In addition, these practices provide opportunities for vulnerable groups, such as women and people with disabilities, to participate in the production value chain. This study shows that the financial independence of SMEs is determined not only by economic factors, but also by their ability to build flexible, fair, and integrated production systems